Glass Film Formation on GOES Surface during High-Temperature Annealing: The Mechanism with Amorphous Phase Formation - Mikhail L. Lobanov; Nikolai N. Nikul’chenkov; Vladimir V. Popov; Artem S. Yurovskikh; Mikhail Yu. Veksler; Vladimir I. Pastukhov (Nanomaterials, 2022)
Ceramic insulation coating (glass film) is an important constituent of grain-oriented electrical steel (GOES) designed for use in transformers. Within the scope of this study, the glass film was obtained by means of interaction between the surface of GOES containing 0.5 wt. % Cu and a heat-resistant MgO coating during annealing up to 1100 °C in the 75%H2 + 25%N2 atmosphere. The structure of glass film was analyzed using X-ray diffraction, glow-discharge optical emission spectroscopy, scanning probe microscopy, scanning electron microscopy, differential scanning calorimetry and thermodynamic calculations. After annealing, the glass film contained the following phases: crystalline (MgFe)2SiO4 and amorphous Fe-based solid solutions. The multi-stage mechanism of the glass film formation on GOES surface during high-temperature annealing was determined.